African-Brazilians and Natives in an Elite University: The Impact of Affirmative Action on Students in Brazil - Oliven, Arabela; Bello, Luciane (Voprosy obrazovaniya / Educational Studies Moscow, 2016)
The best Brazilian universities are public, free of charge, and highly selective. At the beginning of the twenty-first century, many public universities began to earmark spots in all courses for underrepresented groups. The targets of these affirmative action policies were usually students coming from public schools, African-Brazilians, and Natives. This article introduces data on Brazil’s higher education system since its early beginnings: its expansion, segmentation between public and private sectors, and the elitist character of public universities. It points out specificities of race relations in the country since the arrival of the Portuguese, and the historical context that favored the introduction of inclusion policies in public universities. It then deploys qualitative data in order to present the experience of African-Brazilians and Natives who entered an elite university — the Federal University do Rio Grande do Sul — through affirmative action policies. This university is located in the South of the country, the region that has the highest percentage of white population. The analysis focuses on the educational trajectory, family support and expectations, race relations in the university, resilience processes, and plans for the future of a group of racial quota students. By reporting on a pioneering experience, it discusses the importance of diversity in the student body and the challenges the university has to tackle for facing this new reality.